PENGARUH STRUKTUR MODAL, UKURAN PERUSAHAAN, LIKUIDITAS DAN PERTUMBUHAN ASET TERHADAP KINERJA KEUANGAN PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX (JII) PERIODE 2018-2020 - Alfian Fakhri Fauzi; Elen Puspitasari (ITB AAS Indonesia Surakarta, 2021)
This study aims to determine the effect of capital structure, firm size, liquidity, and asset growth on the financial performance of companies listed on the Jakarta Islamic Index (JII) for the 2018-2020 period. Total population in this study is 210 companies. The sampling method used purposive sampling with the criteria of companies listed on JII successively during the 2018-2020 period and publishing financial reports on the Indonesia Stock Exchange (IDX) for 2018-2020. Based on these criteria, 117 observational data were obtained. This study uses multiple linear regression analysis method to see the relationship between variables. The results of hypothesis testing indicate that Capital Structure has a significant negative effect on Financial Performance, Firm Size has a significant negative effect on Financial Performance, Liquidity has a negative but not significant effect on Financial Performance, Asset Growth has a significant positive effect on Financial Performance. Keywords : Financial Performance, Capital Structure, Company Size, Liquidity, and Asset Growth